Impact of foreign direct investment and remittances on Nigeria’s economic performance: An empirical investigation - Orumwense, Evelyn Olubanke; Akanegbu, Benedict; Azu, Nnanna P. (Edelweiss Applied Science and Technology, 2025)
This study investigates the impact of foreign direct investment (FDI) and remittance inflows on Nigeria’s economic performance, measured by GDP per capita, from 1985 to 2023. The research uses both Autoregressive Distributed Lag (ARDL) and Nonlinear ARDL (NARDL) models to capture both symmetric and asymmetric effects in the long and short run. The ARDL model reveals that remittances have a statistically significant long-run positive effect on GDP per capita, with a 1% increase in remittances leading to approximately 0.087% growth. FDI, however, is not significant in the linear long-run model. The NARDL results show stronger and more nuanced findings: positive changes in remittances and FDI significantly increase GDP per capita by 0.096% and 0.245%, respectively, while even negative shocks in both variables yield positive long-run effects of 0.345% for remittances and 0.205% for FDI. In the short run, remittances are insignificant, whereas negative FDI shocks have a significant negative effect, highlighting the economy’s sensitivity to FDI volatility. The results support the extended Solow-Swan growth model, emphasizing the importance of capital inflows. Policymakers should focus on stabilizing FDI, enhancing remittance channels, and reducing external shock vulnerability, as both flows are critical to Nigeria’s long-term economic development.